Nice for What? The Contradictions and Tensions of an Urban District's Racial Equity Transformation - Patricia Virella; Román Liera (MDPI AG, 2024)
Diversity, equity, and inclusion training has exploded over the last decade. While many districts invest considerable resources in developing their leaders' knowledge and skills on equity issues, "niceness" can perpetuate whiteness and present formidable obstacles to meaningful progress. Investigating a large urban-emergent district as a case study, we examine the efforts to eliminate the racial barriers perpetuated by its leaders and explore the contradictions that arise after a year of professional learning geared towards antiracist district transformation. We employ a theory of racialized organizations, seeking to understand how whiteness as niceness impeded school leaders' efforts to engage in antiracist change work. The study provides valuable implications for policy, practice, and future research in education and equity.